Predição do comportamento em ondas de embarcação rápida: limites da linearidade - Souza, Yuri Bastos Rocha de (2020)
This academic work will show the results of computational study using the traditional strip theory of a monohull facing regular head waves. With the experimentalseakeeping data from a prismatic monohull, the proposition of this work is the analisys of the strip theory speed limits which gives correct prediction of motion. For that, computational heave and pitch RAO’s generated by two distinct softwares were compared to experimental heave and pitch RAO’s for the same inertia conditions, wave conditions and speed, which could be identified by: displacement, semi-planing and planing. From this first analisys, a second aproach was did with an update of the weted part of the hull for each speed condition seeking beather results of motion prediction. Following this path, this work tried to investigate the goods or bads influences of this updated aproach over the heave and pitch RAO’s comparing those with the experimental results. Concluding, the computational method gives a reasonable results of motion prediction for considered high speeds. On the other hand, this results were established for non updated weted hull part calculations. This behavior was observed for all contitions of speed leding to believe that this new proposition needs further investigations in the near future.